A hydrothermal method-based coal gasification slag-based microwave absorbing aggregate and preparation method thereof

Through the method based on hydrothermal technology, the reaction activity of aluminosilicate in coal gasification slag is stimulated, and aggregates with high strength and good wave absorption properties are prepared, which solves the problem of insufficient strength and wave absorption properties of coal gasification slag in the existing technology, and realizes the efficient resource utilization of coal gasification slag and the development of green building materials.

CN118637886BActive Publication Date: 2025-03-14ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411120734.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-03-14
Estimated Expiration
2044-08-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively stimulate the reaction activity of aluminosilicate in coal gasification slag, resulting in insufficient strength and absorbing performance of the prepared aggregate, and the inability to fully utilize coal gasification slag.

Method used

Using a method based on hydrothermal technology, coal gasified coarse slag, coal gasified fine slag and calcium carbide slag are mixed and hydrothermal cured to stimulate the reaction activity of silicon tert, and through the optimization of the calcium-silicon ratio and the control of hydrothermal conditions, aggregates with high strength and good absorption properties are formed.

Benefits of technology

The high strength and good microwave absorption performance of coal gasified slag-based absorbing aggregate have been achieved, effectively solving the problems of resource utilization of coal gasified slag and the development of green functional building materials, and reducing the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637886B_ABST
    Figure CN118637886B_ABST
Patent Text Reader

Abstract

The invention discloses a hydrothermal method-based coal gasification slag-based wave-absorbing aggregate and a preparation method thereof, the preparation method comprising mixing and grinding coal gasification coarse slag and carbide slag to obtain a first mixed dry powder; mixing deionized water and the mixed dry powder to obtain a mixed slurry, subjecting the mixed slurry to standard curing and then crushing to obtain a first aggregate pre-finished product; sieving the first aggregate pre-finished product to obtain a second aggregate pre-finished product; and subjecting the second aggregate pre-finished product to hydrothermal curing to obtain a wave-absorbing aggregate finished product. The aggregate prepared by the preparation method has good strength and wave-absorbing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of safe disposal and resource utilization of solid waste, and in particular to a coal gasification slag-based wave-absorbing aggregate based on hydrothermal technology and a preparation method thereof. Background Art

[0002] Among the many ways of utilizing coal, coal gasification is currently a relatively clean and efficient process. However, this process inevitably produces a large amount of coal gasification slag. According to the different slag discharge methods, coal gasification slag can be divided into coal gasification coarse slag and coal gasification fine slag. Among them, the coal gasification coarse slag has a low carbon content, which can be basically ignored, but has a high active aluminosilicate, while the coal gasification fine slag is rich in residual carbon but has low reaction activity. At present, due to the lack of suitable resource utilization technology and processing equipment, coal gasification slag is mainly treated by stockpiling or landfilling, which not only occupies a large amount of land resources, but also causes heavy metal leaching under acid rain erosion, surface water and groundwater infiltration, polluting soil and water resources, which does not meet the requirements of sustainable development. Therefore, it is urgent to find efficient and innovative ways to achieve the safe disposal and resource utilization of coal gasification slag.

[0003] The utilization of coal gasification slag as building materials is the main way to dispose of the huge amount of coal gasification slag. Coal gasification slag contains rich potential gelling active ingredients such as silicate, which can react with other calcium-rich solid waste to produce cement concrete materials. At the same time, the endogenous residual carbon in coal gasification slag is graphitized to varying degrees. Partial graphitization can significantly improve the dielectric properties of carbon materials, making them have the potential for microwave absorption. Therefore, the addition of coal gasification slag can effectively improve the microwave absorption performance of cement concrete materials and give them the ability and characteristics of microwave absorption. However, due to the high content of inert residual carbon in coal gasification slag, the reaction activity of silicate is affected, and it is difficult to directly add a large amount of cement concrete materials. Aggregates, which are in great demand in the construction field, provide a feasible way out. Preparing coal gasification slag into artificial aggregates and then adding them to concrete materials can not only effectively realize the large-scale consumption of coal gasification slag, but also provide a cheaper and more efficient option for the manufacture of functional electromagnetic shielding concrete. It can also alleviate the environmental pressure of excessive resource consumption caused by the mining of natural sand and gravel aggregates, and has both social and economic benefits.

[0004] The invention patent application with publication number CN117229002A discloses a method for preparing cementitious filling materials by stimulating coal gasification slag with desulfurized gypsum. The present invention obtains coal gasification slag ultrafine powder for preparing filling materials by ball milling on the basis of sorting and cleaning coal gasification slag to remove impurities and airing. Then, the coal gangue is crushed and screened by a crusher to obtain coarse aggregate, medium aggregate and fine aggregate for preparing filling materials. Finally, cement, coal gasification slag ultrafine powder, coal gangue aggregate, stimulator and water are mixed evenly to prepare cementitious filling materials. The present invention stimulates the volcanic ash activity of coal gasification slag through desulfurized gypsum, which partially replaces cement to act as a cementitious material. However, the preparation method cannot fully stimulate the reaction activity of coal gasification slag, and the strength of the obtained aggregate has room for further improvement.

[0005] However, the traditional cold-bonded aggregate preparation technology cannot effectively stimulate the reaction activity of aluminosilicates in coal gasification slag, and it is difficult to obtain aggregates with good mechanical properties and microwave absorption properties with the help of additives. Therefore, seeking a preparation method for coal gasification slag-based functional artificial aggregate to obtain artificial aggregates with high mechanical properties and good microwave absorption properties is of great significance for the resource utilization of coal gasification slag and the development of green functional building materials. Summary of the invention

[0006] A method for preparing coal gasification slag-based microwave-absorbing aggregate based on a hydrothermal method. The aggregate prepared by the method has good strength and microwave-absorbing performance.

[0007] The present invention provides a method for preparing coal gasification slag-based wave-absorbing aggregate based on a hydrothermal method, comprising:

[0008] S1, mixing and grinding coal gasification coarse slag, coal gasification fine slag and carbide slag to obtain a first mixed dry powder;

[0009] S2, mixing deionized water and the first mixed dry powder of step S1 to obtain a mixed slurry, performing standard curing on the mixed slurry and then crushing it to obtain a first aggregate pre-finished product;

[0010] S3, screening the first aggregate pre-finished product of step S2 to obtain a second aggregate pre-finished product;

[0011] S4. Performing hydrothermal curing on the second aggregate pre-finished product to obtain a wave-absorbing aggregate finished product.

[0012] Preferably, the temperature of the hydrothermal curing is 180-210°C.

[0013] As the hydrothermal curing temperature increases, the reactivity of aluminosilicates in the gasification slag is stimulated, and reacts with calcium-rich carbide slag to generate a large amount of gel and crystal products, thereby effectively improving the mechanical properties of the aggregate. At the same time, the appropriate hydrothermal curing temperature can form a relatively strong skeleton, so that the light waves irradiated to the skeleton are reflected multiple times, thereby enhancing the microwave absorption performance of the aggregate.

[0014] The hydrothermal curing temperature is too low to effectively stimulate the reaction activity of aluminosilicates in coal gasification slag. The gel and crystal products generated by the reaction are relatively small, and the mechanical properties of the aggregate are also poor.

[0015] Further preferably, the heating time of the hydrothermal curing is 90-120 min, the heating time is 630-720 min, and the cooling time is 360-480 min.

[0016] Preferably, the raw materials of the coal gasification coarse slag and the carbide slag are mixed with a calcium-silicon ratio of 0.8-1.4. The aggregate prepared by mixing the calcium-silicon ratio within this range has a more stable structure and better mechanical properties after hydrothermal curing.

[0017] Preferably, in step S1, coal gasification fine slag is introduced, mixed with coal gasification coarse slag and carbide slag, and ground to obtain a second mixed dry powder, wherein the residual carbon content of the second mixed dry powder is 10-20%.

[0018] The coal gasification fine slag provided by the present invention includes a large amount of residual carbon and a certain amount of aluminosilicate. The aluminosilicate can react with alkaline calcium-rich carbide slag to form gel. In this process, the residual carbon is separated from the aluminosilicate and evenly distributed in the gel structure, thereby enhancing the wave absorption performance of the aggregate. In order to avoid excessively high residual carbon content and insufficient aluminosilicate, resulting in too low gel content and affecting the strength of the aggregate, the present invention adds coal gasification coarse slag enriched with highly active aluminosilicate to retain an appropriate amount of gel, thereby ensuring that the aggregate has appropriate strength. At the same time, the present invention further enhances the strength and wave absorption performance of the aggregate through hydrothermal curing.

[0019] Furthermore, the coal gasification coarse slag, coal gasification fine slag and carbide slag are mixed with a calcium-silicon ratio of 0.8-1.4.

[0020] Furthermore, the coarse coal gasification slag, fine coal gasification slag and carbide slag in step S1 are dried before mixing, the drying temperature is 60-90° C., and the drying time is 24-48 h to prevent the moisture contained in the raw materials themselves from affecting the subsequent ball milling process, thereby weakening the effect of ball milling.

[0021] Furthermore, the grinding is ball milling, the rotation speed of the ball mill is 400-500 r / min, and the time is 60-120 min.

[0022] Furthermore, the ball-milled powder needs to be placed in a forced air drying oven for secondary drying at a drying temperature of 60°C for at least 24 h. The raw materials need to be taken out and weighed every 1 h for the last 6 h of the drying process. Drying can be stopped only after two consecutive weighings to a constant weight, so as to avoid bringing excess moisture into subsequent reactions, thereby affecting the performance of the aggregate product.

[0023] Furthermore, the powder after secondary drying is sieved through a 100-mesh (150 μm) standard sieve, and the sieved raw material powder is used as a reaction raw material for subsequent use.

[0024] In step S2:

[0025] Furthermore, the mass ratio of the deionized water to the mixed dry powder of step S1 is 0.4-0.45.

[0026] Furthermore, the temperature of the standard curing is 20±2°C, and the relative humidity is ≥95%. The specific time of the standard curing depends on the hardening degree of the specimen, and the termination standard is complete and smooth demoulding. The demoulding time of the same batch of test blocks must be kept consistent. Preferably, the standard curing time is 24-48 h.

[0027] Furthermore, the blocks obtained after standard curing are crushed, and the crushers used in the crushing process are impact crushers, jaw crushers, etc.

[0028] In step S3:

[0029] Furthermore, the first aggregate pre-product was sieved using 2.36 mm, 4.75 mm, 9.5 mm, 16 mm and 20 mm standard sieves to obtain a second aggregate pre-product containing coarse aggregate with a particle size of 4.75-20 mm and fine aggregate with a particle size of 2.36-4.75 mm.

[0030] In step S4:

[0031] Furthermore, the finished absorbing aggregate after hydrothermal curing is dried at a temperature of 40-60° C. and a drying time of at least 6-12 h.

[0032] In another aspect, the present invention further provides a coal gasification slag-based absorbing aggregate, which is prepared by the method for preparing the coal gasification slag-based absorbing aggregate based on the hydrothermal method.

[0033] The mechanism of the present invention is:

[0034] The present invention provides a new way to safely dispose of and recycle coal gasification slag. Based on the complementary mechanism of chemical components between different solid wastes, the fine coal gasification slag, coarse coal gasification slag and carbide slag are synergistically recycled and converted into artificial aggregates by scientifically optimizing the composition. Based on the design concept of directional low-carbon functional building materials, the present invention innovatively utilizes the characteristics of coal gasification slag rich in aluminosilicates and residual carbon, gives full play to the potential gelling activity of aluminosilicates in coal gasification slag and the microwave absorption characteristics of graphitized residual carbon, and converts it into functional artificial aggregate with microwave absorption ability. In order to further promote the reaction, the present invention also innovatively proposes to use medium and low temperature hydrothermal conversion technology to stimulate the reaction activity of solid waste raw materials, induce the reaction raw materials to generate stable gel and crystal products in situ, and ensure that the artificial aggregate has excellent mechanical properties. At the same time, it can also achieve efficient solidification of pollutants such as heavy metals in solid waste raw materials through the synergistic effect of various physical and chemical mechanisms such as physical isolation and chemical bonding. Compared with the traditional coal gasification slag disposal method, the present invention not only greatly reduces the environmental risks such as surface dust, water and heavy metal pollution caused by the landfill method, but also more effectively absorbs two major types of solid wastes, coal gasification slag and carbide slag, and converts them into functional wave-absorbing artificial aggregates with excellent mechanical properties. It also further reduces the mining of natural sand and gravel aggregates, has both social and economic benefits, and provides a new green, low-carbon and sustainable development plan for the safe disposal and resource utilization of solid waste.

[0035] Compared with the prior art, the beneficial effects of the present invention are:

[0036] The present invention forms a skeleton structure with higher strength by performing hydrothermal curing on the second aggregate pre-finished product. When electromagnetic waves are incident on the skeleton, the electromagnetic wave energy is attenuated due to the reflection and absorption of the aggregate, thereby obtaining a wave-absorbing aggregate finished product with higher strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A flow chart of a method for preparing coal gasification slag-based wave-absorbing aggregate based on hydrothermal technology proposed in a specific embodiment of the present invention;

[0038] Figure 2 A schematic diagram of the process flow of a method for preparing coal gasification slag-based microwave-absorbing aggregate based on hydrothermal technology proposed in a specific embodiment of the present invention. DETAILED DESCRIPTION

[0039] The present invention provides a coal gasification slag-based wave absorbing aggregate based on hydrothermal technology and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail by examples below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] Embodiment 1:

[0041] A coal gasification slag-based microwave absorbing aggregate based on hydrothermal technology and a preparation method thereof, such as Figure 1 and Figure 2 As shown, the specific steps are as follows:

[0042] (1) Coal gasification slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h. They were taken out and placed in a ball mill to be fully mixed with agate balls with continuous particle size distribution. The raw material powders were then ball milled in a planetary ball mill at a speed of 500 r / min for 30 min for both forward and reverse rotations.

[0043] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material is taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0044] (3) The coal gasification slag obtained in step (2) and the carbide slag powder are mixed at a calcium-silicon ratio of 1.2, and uniformly mixed for 2 minutes under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0045] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0046] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0047] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 180°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0048] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0049] The finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregates and Their Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 1:

[0050] Table 1 Physical properties of aggregates in Example 1

[0051]

[0052] Embodiment 2:

[0053] A coal gasification slag-based microwave absorbing aggregate based on hydrothermal technology and a preparation method thereof, the specific steps are as follows:

[0054] (1) Coal gasification slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h. They were taken out and placed in a ball mill to be fully mixed with agate balls with continuous particle size distribution. The raw material powders were then ball milled in a planetary ball mill at a speed of 500 r / min for 30 min for both forward and reverse rotations.

[0055] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material is taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0056] (3) The coal gasification slag and carbide slag powders obtained in step (2) are mixed at a calcium-silicon ratio of 1.2, and uniformly mixed for 2 min under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0057] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0058] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0059] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 210°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0060] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0061] The obtained finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregate and Its Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 2:

[0062] Table 2 Physical properties of aggregates in Example 2

[0063]

[0064] Embodiment 3:

[0065] A coal gasification slag-based microwave absorbing aggregate based on hydrothermal technology and a preparation method thereof, the specific steps are as follows:

[0066] (1) Coal gasification fine slag, coal gasification coarse slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h, taken out, put into a ball mill and fully mixed with agate balls with continuous particle size distribution, and then the raw material powders were ball milled separately using a planetary ball mill. The speed of the planetary ball mill was 500 r / min, and the forward and reverse rotation were 30 min each.

[0067] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material needs to be taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0068] (3) The coal gasification fine slag, coal gasification coarse slag and carbide slag powders obtained in step (2) are mixed at a calcium-silicon ratio of 1.2 and a residual carbon content of 10%, and uniformly mixed for 2 minutes under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0069] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0070] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0071] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 180°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0072] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0073] The finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregates and Their Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 3:

[0074] Table 3 Physical properties of aggregates in Example 3

[0075]

[0076] Embodiment 4:

[0077] In this embodiment, the selection of coal gasification fine slag, coal gasification coarse slag and carbide slag is the same as that in Embodiment 1.

[0078] The operation process of this embodiment is consistent with that of embodiment 1, and some parameters in each step are adjusted as follows:

[0079] (1) Coal gasification fine slag, coal gasification coarse slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h, taken out, put into a ball mill and fully mixed with agate balls with continuous particle size distribution, and then the raw material powders were ball milled separately using a planetary ball mill. The speed of the planetary ball mill was 500 r / min, and the forward and reverse rotation were 30 min each.

[0080] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material needs to be taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0081] (3) The coal gasification fine slag, coal gasification coarse slag and carbide slag powders obtained in step (2) are mixed at a calcium-silicon ratio of 1.2 and a residual carbon content of 20%, and uniformly mixed for 2 minutes under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0082] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0083] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0084] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 180°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0085] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0086] The finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregates and Their Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 4:

[0087] Table 4 Physical properties of aggregates in Example 4

[0088]

[0089] Comparative Example 1:

[0090] A coal gasification slag-based microwave absorbing aggregate based on hydrothermal technology and a preparation method thereof, the specific steps are as follows:

[0091] (1) Coal gasification slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h. They were taken out and placed in a ball mill to be fully mixed with agate balls with continuous particle size distribution. The raw material powders were then ball milled in a planetary ball mill at a speed of 500 r / min for 30 min for both forward and reverse rotations.

[0092] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material is taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0093] (3) The coal gasification slag and carbide slag powders obtained in step (2) are mixed at a calcium-silicon ratio of 1.2, and uniformly mixed for 2 min under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0094] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0095] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0096] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 150°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0097] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0098] The finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregates and Their Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 5:

[0099] Table 5 Physical properties of aggregates of Comparative Example 1

[0100]

[0101] Comparative Example 2:

[0102] In this comparative example, the selection of coal gasification coarse slag and carbide slag is the same as that in Example 2.

[0103] The operation process of this comparative example is different from that of Example 2 in that the hydrothermal curing system is no longer used in this comparative example, and each step is adjusted as follows:

[0104] (1) Coal gasification slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h. They were taken out and placed in a ball mill to be fully mixed with agate balls with continuous particle size distribution. The raw material powders were then ball milled in a planetary ball mill at a speed of 500 r / min for 30 min for both forward and reverse rotations.

[0105] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material is taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0106] (3) The coal gasification slag obtained in step (2) and the carbide slag powder are mixed at a calcium-silicon ratio of 1.2, and uniformly mixed for 2 minutes under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0107] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0108] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0109] (6) The second aggregate pre-finished product obtained in step (5) is placed in a sealed bag, reopened, and placed in a standard curing box for further sealed curing (temperature 20±2°C, relative humidity ≥95%) for 26 days, i.e., the total curing age is 28 days.

[0110] (7) The artificial aggregate obtained in step (6) after standard curing for 28 days is taken out and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0111] The obtained finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregate and Its Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 6:

[0112] Table 6 Physical properties of aggregates in comparative example 2

[0113]

[0114] Comparative Example 3:

[0115] In this comparative example, the selection of coal gasification coarse slag, coal gasification fine slag and carbide slag is the same as that in Example 4.

[0116] The operating process of this comparative example is different from that of Example 4 in that the amount of residual carbon added in this comparative example reaches 30%, and each step is adjusted as follows:

[0117] (1) Coal gasification fine slag, coal gasification coarse slag and carbide slag were placed in a blast dryer and dried at 60 °C for 24 h, taken out, put into a ball mill and fully mixed with agate balls with continuous particle size distribution, and then the raw material powders were ball milled separately using a planetary ball mill. The speed of the planetary ball mill was 500 r / min, and the forward and reverse rotation were 30 min each.

[0118] (2) The raw material powder after ball milling is taken out, sieved through a standard sieve and separated from the agate balls. The separated raw material powder is placed in a forced air drying oven at 60 °C for secondary drying for at least 24 h. During the last 6 h of the drying process, the raw material is taken out and weighed once every 1 h until it is weighed at a constant weight for 2 consecutive times. The drying can be stopped. The dried raw material powder is sieved through a 100 mesh (150 μm) standard sieve and the sieved raw material powder is used as the reaction raw material for subsequent use.

[0119] (3) The coal gasification fine slag, coal gasification coarse slag and carbide slag powders obtained in step (2) are mixed at a calcium-silicon ratio of 1.2 and a residual carbon content of 30%, and uniformly mixed for 2 minutes under the action of a stirrer at a speed of 200 r / min to obtain a mixed dry powder.

[0120] (4) The mixed dry powder obtained in step (3) was mixed with deionized water in a ratio of 1.0:0.4, and stirred for 5 min under the action of a stirrer at a speed of 500 r / min to obtain a fresh slurry, which was immediately injected into a 100 mm×100 mm×100 mm plastic mold. Appropriate pressure and vibration were applied to reduce the bubbles and filler pores inside the specimen. To prevent water loss, a plastic film was used for sealing. The clean slurry was promptly placed in a standard curing box for sealed curing (temperature 20±2°C, relative humidity ≥95%) for 48 h before demolding.

[0121] (5) The hardened specimen obtained in step (4) is placed in a crusher and crushed into a first aggregate pre-product having a continuous particle size distribution. The first aggregate pre-product is then sieved using standard sieves of 2.36 mm, 4.75 mm, 9.5 mm, 16 mm, and 20 mm to obtain a second aggregate pre-product.

[0122] (6) The second aggregate pre-finished product obtained in step (5) is placed in a hydrothermal kettle for hydrothermal curing. The temperature of the hydrothermal reaction is 180°C. The heating time of the hydrothermal kettle is 90 min, the heating time is 630 min, and the cooling time is 360 min.

[0123] (7) The artificial aggregate obtained in step (6) after hydrothermal curing is taken out after cooling, and placed in a forced air drying oven for drying at a drying temperature of 60° C. for a drying time of at least 6 h. After drying, a finished aggregate is obtained, which can be used for the preparation of building materials such as aggregate concrete and concrete pavement bricks.

[0124] The obtained finished aggregate was tested for performance according to GB / T 17431.1-2010 "Lightweight Aggregate and Its Test Methods". The absorption loss of the finished aggregate was tested by a vector network analyzer. The test frequency range was 2 GHz-18 GHz. The test results are shown in Table 7:

[0125] Table 7 Physical properties of aggregates in comparative example 3

[0126]

[0127] By comparing Comparative Example 1, Comparative Example 2 with Example 1, Example 2, Example 3, and Example 4, it can be found that the cylinder pressure strength and absorption loss of the artificial aggregates prepared in Comparative Example 2 with standard curing and Comparative Example 1 with hydrothermal oxidation curing at a lower temperature are both low, while the cylinder pressure strength and absorption loss of the artificial aggregates prepared in Examples 1 to 4 are significantly improved, especially after the addition of coal gasification fine slag with a higher residual carbon content, the wave absorption performance is significantly improved.

[0128] In Comparative Example 3, the residual carbon content is too high. Although the absorption loss is significantly increased, the strength of the aggregate is significantly decreased. Therefore, although the residual carbon has a significant effect on improving the microwave absorption performance of artificial aggregate, it is still necessary to control the amount of residual carbon so as to achieve a balance between the mechanical properties and microwave absorption performance of artificial aggregate.

[0129] The above is only a preferred embodiment of the present invention. Although the present invention has been disclosed as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the above disclosed methods and technical contents without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing coal gasification slag-based microwave absorbing aggregate based on a hydrothermal method, characterized in that: include: S1, mixing and grinding coal gasification fine slag, coal gasification coarse slag and carbide slag to obtain a second mixed dry powder, wherein the residual carbon content of the second mixed dry powder is 10-20wt%; S2, mixing deionized water and the second mixed dry powder of step S1 to obtain a mixed slurry, performing standard curing on the mixed slurry and then crushing it to obtain a first aggregate pre-finished product; S3, screening the first aggregate pre-finished product of step S2 to obtain a second aggregate pre-finished product; S4. Performing hydrothermal curing on the second aggregate pre-finished product to obtain a wave-absorbing aggregate finished product, wherein the temperature of the hydrothermal curing is 180-210°C.

2. According to the method for preparing coal gasification slag-based wave-absorbing aggregate based on the hydrothermal method of claim 1, the heating time of the hydrothermal curing is 90-120 min, the heating time is 630-720 min, and the cooling time is 360-480 min.

3. The method for preparing coal gasification slag-based microwave absorbing aggregate based on a hydrothermal method according to claim 1, characterized in that: The coal gasification fine slag, coal gasification coarse slag and carbide slag are mixed with a calcium-silicon ratio of 0.8-1.

4.

4. According to the method for preparing coal gasification slag-based absorbing aggregate based on a hydrothermal method according to claim 1, the coal gasification coarse slag, coal gasification fine slag and carbide slag in step S1 are dried before mixing, the drying temperature is 60-90°C, and the drying time is 24-48h.

5. The method for preparing coal gasification slag-based microwave absorbing aggregate based on a hydrothermal method according to claim 1, wherein the grinding is ball milling, the rotation speed of the ball mill is 400-500 r / min, and the time is 60-120 min.

6. According to the method for preparing coal gasification slag-based microwave absorbing aggregate based on a hydrothermal method according to claim 1, the mass ratio of the deionized water to the mixed dry powder of step S1 is 0.4-0.

45.

7. A coal gasification slag-based microwave absorbing aggregate, characterized in that: The material is prepared by the method for preparing coal gasification slag-based wave-absorbing aggregate based on a hydrothermal method as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for preparing cemented filling material by using desulfurized gypsum to excite coal gasification slag

    CN117229002A

  • Lightweight aggregate based on coarse coal gasification slag and preparation method thereof

    CN109608074A

  • Coal-based wave-absorbing material, preparation method and wave-absorbing application

    CN114181663A